PENGARUH KUALITAS PELAYANAN, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI PADA JASA PELATIHAN UVI CONSULTANT YOGYAKARTA) - Suhartono Suhartono Suhartono; Dwi Rahayu (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
ABSTRACT Services are basically intact and leave no ownership whatsoever. A large business competition in the service industry requires that companies work hard to understand the needs and wants of their customers. How companies can improve their services professionally, so that consumers are satisfied with what they have gained that they can create loyalty. The research aims to know whether the quality of services, prices, quality of products and consumer satisfaction affect customer loyalty and whether consumer satisfaction can be increased between service quality, price, product quality to customer loyalty in the uvi temple service. The population in this research is all the customers who have used training services at uvi consultants. The sample in the study numbered 200, using a factory-bound approach, a sample withdrawal method based on a given consideration. The method of data collection used in this study is questionnaires and USES the likert scale. The results of the tests indicate that the quality of service, price and quality have a positive and significant impact on consumer satisfaction. Service quality, price, product quality and consumer satisfaction also have a positive and significant impact on customer loyalty. With a path analysis or analysis of the magnitude of the indirect influence is greater than the direct influence so the consumer satisfaction is capable of mitigating between the impact of the quality of service, the price and the quality of the product on customer loyalty. Key words: service quality, price, product quality, consumer satisfaction and customer loyalty